Heart rate reactivity to mental stress in athlete and non-athlete children - Ábel, K.; Szabó, A. R.; Szabo, A. (Baltic Journal of Sport and Health Sciences, 2020)
Background. Research suggests that exercise training and/or physical fitness may be associated with lower heart rate reactivity and faster recovery from psychosocial stress. This relationship was rarely studied in children despite the potential protective role of physical activity in stress that may start in early life stages.